Genetically-encoded fragment-based discovery of glycopeptide ligands for DC-SIGN. Issue 19 (15th October 2018) - Ng, Simon; Bennett, Nicholas James; Schulze, Jessica; Gao, Nan; Rademacher, Christoph; Derda, Ratmir
Graphical abstract: Abstract: We have employed genetically-encoded fragment-based discovery to identify novel glycopeptides with affinity for the dendritic cell receptor DC-SIGN. Starting from libraries of 10 8 mannose-conjugated peptides, we identified glycopeptides that exhibited up to a 650-fold increase in multivalent binding affinity for DC-SIGN, which is also preserved in cells. Monovalently, our most potent glycopeptides have a similar potency to a Man3 oligosaccharide, representing a 15-fold increase in activity compared to mannose. These compounds represent the first examples of glycopeptide ligands that target the CRD of DC-SIGN. The natural framework of glycopeptide conjugates and the simplicity of orthogonal conjugation to make these glycopeptides anticipates a promising future for development of DC-SIGN-targeting moieties.